SOME REFLECTIONS ON THE IMPORTANCE OF WATER IN THE UZBEK KHANATE STATEHOOD SYSTEM - Mulladjanova Rano Abdulladjanovna (American Journals Publishing, 2022)
In this article, the importance of water in the state system of the Uzbek khanates are extremely great, from a historical point of view, what was the water supply of the population of the Uzbek khanates, the state of the Aral Sea from the earliest times to the end of the 17th century, the changes that occurred in its basin at the end of the 19th century and attention was paid to its consequences.
Keywords: ecology, water problem, irrigation system, water bodies, reservoirs